LIBRARY INFORMATION SYSTEM (SIIPETAKA) IN SMK KEBAYORAN BARU AL-KAUTSAR - Estu Mulia Warna Diyanti; Duwi Cahya Putri Buani (Jurnal Techno Nusa Mandiri, 2019)
SMK Al-Kautsar Kebayoran Baru Library is a library that supports the teaching and learning process, many of the students and teachers of AL-Kautsar Vocational School want to buy books in the book library, and the service is slow because the system is still conventional. Therefore the AL-Kautsar Vocational Library needs an Information System that is able to solve all the problems needed above. Then made SIIPETAKA or SMK Al-Kautsar Library Information System. SIIPETAKA is a system designed to facilitate the recording of data in the Al-Kautsar Vocational Library, SIIPETAKAN was designed using the Waterfall method or model, the Waterfall Model is one of the models used to use Information Systems. Every step in the waterfall method is easy to follow and using the Waterfall model the program design documentation is well documented. With SIIPETAKA, it is expected that problems that occur such as data loss, it is difficult to find member data and book data can be resolved properly.